Screening the antigenic properties of Porphyromonas gingivalis and level of raised antibodies after antigenic injection into Balb/c Mice - Mahdi T Khadematolrasoul; Farin Kiany; Faezeh Saadati (Wolters Kluwer Medknow Publications, 2017)
Background: Different diagnostic screening tests have been developed to detect periodontal disease in the early stages. Despite these advances still, there is a need for a more practical and beneficial diagnostic test. Aim: The aim of this study was to investigate the possibility of developing such a kit based on the body immune response against Porphyromonas gingivalis. Method and Materials: This experimental study was conducted by culturing P. gingivalis and extracting its antigens. These antigens were injected into peritoneal cavity of four Balb/c mice. Finally, the pattern, type, and quantity of antibody response against P. gingivalis antigen were detected. Results of the study showed that 3.0 × 108 cells of P. gingivalis are an appropriate count for stimulating the immunization in Balb/c mice and the subsequent amount of antibody (IgG) production was 81.5 μg/ml. Result: The antigenic injections which were done in the current study could mimic the condition of periodontal disease and the raise of P. gingivalis in the body. Conclusion: The obtained data can be used in future attempts to develop practical and usable test kits against P. gingivalis.